Real-time observation of intersystem crossing induced by charge recombination during bimolecular electron transfer reactions. (January 2017) - Alsam, Amani A.; Aly, Shawkat M.; Parida, Manas R.; Alarousu, Erkki; Cao, Zhen; Cavallo, Luigi; Mohammed, Omar F.
Abstract: Real-time probing of intersystem crossing (ISC) and triplet-state formation after photoinduced electron transfer (ET) is a particularly challenging task that can be achieved by time-resolved spectroscopy with broadband capability. Here, we examine the mechanism of charge separation (CS), charge recombination (CR) and ISC of bimolecular photoinduced electron transfer (PET) between poly[(9, 9-di(3, 3′-N, N'-trimethyl-ammonium) propyl fluorenyl-2, 7-diyl)-alt-co-(9, 9-dioctyl-fluorenyl-2, 7-diyl)] diiodide salt (PFN) and dicyanobenzene (DCB) using time-resolved spectroscopy. PET from PFN to DCB is confirmed by monitoring the transient absorption (TA) and infrared spectroscopic signatures for the radical ion pair (DCB ─ -PFN + ). In addition, our time-resolved results clearly demonstrate that CS takes place within picoseconds followed by CR within nanoseconds. The ns-TA data exhibit the clear spectroscopic signature of PFN triplet-triplet absorption, induced by the CR of the radical ion pairs (DCB ─ -PFN + ). As a result, the triplet state of PFN ( 3 PFN*) forms and subsequently, the ground singlet state is replenished within microseconds. Graphical abstract: Highlights: Excited state bimolecular electron transfer monitored by time-resolved laser spectroscopy with broadband capability. The formation of triplet state induced by charge recombination process in bimolecular reaction. Static photo-induced electron transfer process is evident.